2003
DOI: 10.1097/01.tp.0000048380.84355.4a
|View full text |Cite
|
Sign up to set email alerts
|

Immature rat myeloid dendritic cells generated in low-dose granulocyte macrophage-colony stimulating factor prolong donor-specific rat cardiac allograft survival

Abstract: Our data confirming the immunoregulatory effect of immature DCs indicate that induction of transplant tolerance by iMDCs is partly dependent on in vivo generation of regulatory T cells. This finding suggests that immunization with immature donor DCs has therapeutic potential for the induction of transplant tolerance and treatment of autoimmune diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 31 publications
2
49
1
1
Order By: Relevance
“…Both observations suggest that DC maturation per se is not necessarily the distinguishing feature of immunogenic as opposed to tolerogenic DCs (46). Despite these reservations, data suggest that immature myeloid precursors of DC suppress T cell activation while immature DCs support Treg development, and mature DCs can override Treg-mediated suppression in vitro and in vivo (47)(48)(49). We had reported that preferential induction of Treg by DCs activated by alternate CD200Rs was an important feature of the effect of CD200 interaction with alternate CD200R isoforms (29).…”
Section: Discussionmentioning
confidence: 77%
“…Both observations suggest that DC maturation per se is not necessarily the distinguishing feature of immunogenic as opposed to tolerogenic DCs (46). Despite these reservations, data suggest that immature myeloid precursors of DC suppress T cell activation while immature DCs support Treg development, and mature DCs can override Treg-mediated suppression in vitro and in vivo (47)(48)(49). We had reported that preferential induction of Treg by DCs activated by alternate CD200Rs was an important feature of the effect of CD200 interaction with alternate CD200R isoforms (29).…”
Section: Discussionmentioning
confidence: 77%
“…Drugs that prevent full activation of APC during primary sensitization may be better candidates than conventional immunosuppressive agents that broadly inhibit T lymphocytes activation. Indeed, many reports suggest that maintaining DC in an immature or semi-mature stage can be effective in preventing allograft rejection and favor graft tolerance [22,23]. Various compounds such as MMF, vitamin D or glucocorticoids have been shown to inhibit DC maturation, but all these drugs also strongly inhibit T cell activation [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Several protocols have been proposed to generate in vitro tolerogenic DCs using specific culture conditions, pharmacologic treatment (exposure to immunosuppressive drugs or cytokines), or genetic manipulation (3)(4)(5)(6)(7)(8)(9). These DCs can be of donor or recipient origin, and their capacity to modulate alloimmune responses and induce tolerance was demonstrated in various experimental transplant models (5,(9)(10)(11)(12)(13)(14). The mode of action of these tolerogenic DCs resides in their ability to induce T cell hyporesponsiveness to the alloantigens and/or to favor the expansion/generation of CD4 +…”
mentioning
confidence: 99%